Income diversification and liquidity risk in ASEAN-5 banks: A Bayesian perspective. - Quynh Nga Duong; Nguyen Thuy Khue Tran; Thi Phuong Thao Dang (PLoS ONE)
Our research employed Bayesian linear regression utilizing an adaptive Metropolis-Hastings method with Gibbs sampling to assess the influence of bank income diversification on the liquidity risk of five ASEAN banks. The results indicate a positive relationship between bank liquidity risk and income diversification, as well as loan interest rates. This implies that banks with greater income diversification tend to have higher liquidity ratios and reduce the bank risk and conversely. Therefore, the study suggests that banks should enhance their diversification efforts to mitigate their liquidity risk.